2022
DOI: 10.1093/conphys/coac002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of temperature optimum signatures of corals at both latitudinal extremes of the Red Sea

Abstract: Rising ocean temperatures are pushing reef-building corals beyond their temperature optima (Topt), resulting in reduced physiological performances and increased risk of bleaching. Identifying refugia with thermally resistant corals and understanding their thermal adaptation strategy is therefore urgent to guide conservation actions. The Gulf of Aqaba (GoA, northern Red Sea) is considered a climate refuge, hosting corals that may originate from populations selected for thermal resistance in the warmer waters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 89 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…To gauge the presence of photosymbionts and estimate the photosynthetic potential of each sponge species we obtained several fresh representative samples of ~ 5 square cm from each sponge taxa and transferred them in seawater to the lab, where they were qualitatively examined using an Imaging‐PAM (Walz GmbH, Effeltrich, Germany) for the presence of photosynthetic activity by measuring the maximum photochemical efficiency (Fv/fm) as described in Banc‐Prandi et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…To gauge the presence of photosymbionts and estimate the photosynthetic potential of each sponge species we obtained several fresh representative samples of ~ 5 square cm from each sponge taxa and transferred them in seawater to the lab, where they were qualitatively examined using an Imaging‐PAM (Walz GmbH, Effeltrich, Germany) for the presence of photosynthetic activity by measuring the maximum photochemical efficiency (Fv/fm) as described in Banc‐Prandi et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…levels of response of a physiological variable) to thermal stress across populations, could be modulated by thermal history, in particular by temperature variability. Studies showed that thermal performances of scleractinians can vary across latitudes (Astrangia poculata, Aichelman et al, 2019; Orbicella franksi, Silbiger et al, 2019;Stylophora pistillata, Acropora muricata, Porites lobata, Seriatopora hystrix, and Pocillopora verrucosa;Banc-Prandi et al, 2022) and seasons (Porites cylindrical and Acropora valenciennesi; Jurriaans et al, 2019), due to thermal adaptation/acclimatization. Studies that have compared thermal sensitivities of scleractinians across depths either found no differences in thermal sensitivity (instantaneous acute heat stress, 5-10 vs. 30-35m;Gould et al, 2021), higher sensitivity (ramping of 1°C/day; 20 vs. 43m; Frates et al, 2021) or lower sensitivity (ramping of 1°C/hour; 25 vs. 85m; Godefroid et al, 2023) in mesophotic colonies.…”
Section: Introductionmentioning
confidence: 99%